الرضا الوظيفي وعلاقته بدافعية الانجاز لأساتذة التربية البدنية والرياضية - تمشباش, محمد; مساحلى, الصغير (جامعة الوادي - University of Eloued, 2022)
هدفت الدراسة الى التعرف على مستوى الرضا الوظيفي دافعية الانجاز لدى اساتذة التربية البدنية والرياضية، ومعرفة طبيعة العلاقة بينهما، واستخدم الباحثان المنهج الوصفي بشقه الارتباطي الملائم لطبيعة الدراسة، وجرت الدراسة على عينة مكونة من اساتذة التربية البدنية والرياضية للمقاطعة الثانية بولاية بسكرة قدرها 37 استاذ تعليم ثانوي، ولجمع المعلومات والبيانات حول الظاهرة تم استعمال مقياسي الرضا الوظيفي ودافعية الانجاز، وبعد المعالجة الاحصائية توصلنا الى ان مستوى الرضا الوظيفي ودافعية الانجاز للأساتذة كان متوسط، ووجود علاقة ارتباطية طردية ضعيفة جدا بين الرضا الوظيفي ودافعية الانجاز للأساتذة. Abstract : The aim of this is to identify the level of job satisfaction and motivation of achievement among the teachers of Physical Education and Sports teachers and to describe the nature of the relationship existing between them. The researchers used the descriptive approach, which is closely related to the nature of the study. The study was conducted on a sample of 37 secondary education teachers who teach physical education and sports in the second province of Biskra. To collect information and data about the phenomenon, we have used both measures of job satisfaction and motivation to achievement. After statistical processing, we found that the level of job satisfaction and achievement motivation of the teachers was average, with a very weak correlation between job satisfaction and the motivation to achievement for the teachers.
دراسة ميدانية لأساتذة التربية البدنية والرياضية للمقاطعة 2 بولاية بسكرة
مقال
Keywords: رضا وظيفي ؛ دافعية انجاز ؛ استاذ تربية بدنية ورياضية ؛ حصة تربية بدنية ورياضية; Job satisfaction؛ Motivation of achievement؛ Physical Education and Sports teachers؛ Physical Education and Sports Classes